2014
DOI: 10.1093/alcalc/agu095
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Alcohol Use Disorders Identification Test for Detecting Problem Drinking in 18–35 Year-Olds in England: Method Comparison Study

Abstract: The full AUDIT scale showed good or very good accuracy for all outcome measures for males and females, except for alcohol abuse which had sufficient accuracy. In a screening scenario where sensitivity might be prioritized, the optimal cut-point is lower than established AUDIT cut-points of 8+ for men and 6+ for women. Bayes' Theorem to calculate individual probabilities for problem drinking offers an alternative to arbitrary cut-point threshold scores in screening and brief intervention programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Subjects in the CTR group were excluded after screening for alcohol dependence or alcohol abuse, but no information regarding number of drinks or AUDIT score was collected. However, several studies indicate that AUDIT and DSM-IV have similar specificity (Dawson et al, 2012; Foxcroft et al, 2015) providing evidence that subjects in the CTR group were likely assigned to the correct group. A second limitation of the current study is the lack of inclusion of other measures that could have been useful to distinguish among the four sample groups.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects in the CTR group were excluded after screening for alcohol dependence or alcohol abuse, but no information regarding number of drinks or AUDIT score was collected. However, several studies indicate that AUDIT and DSM-IV have similar specificity (Dawson et al, 2012; Foxcroft et al, 2015) providing evidence that subjects in the CTR group were likely assigned to the correct group. A second limitation of the current study is the lack of inclusion of other measures that could have been useful to distinguish among the four sample groups.…”
Section: Discussionmentioning
confidence: 99%
“…The AUROC results in our study suggested that the AUDIT-KR was an appropriate diagnostic tool for screening for AUD according to DSM-5 criteria. A previous article from the United Kingdom reported that the AUDIT was useful for AUD screening in both genders, ranging in age from 18 to 35 years according to DSM-5 criteria (males: AUROC, 0.70; 95% CI, 0.60 to 0.78; females: AUROC, 0.73; 95% CI, 0.67 to 0.78) 15). The AUROC results in that article were lower than the results found by our study.…”
Section: Discussionmentioning
confidence: 99%
“…College students with drinking problems as indicated by higher AUDIT scores showed impulsive decision making in a discounting task and diminished inhibitory control in a go/no-go task (Murphy and Garavan, 2011). The AUDIT score has been used as an outcome measure to identify young adults who developed alcohol dependence (Foxcroft et al, 2015), and to evaluate at-risk drinking in individuals with comorbid depression (van den Berg et al, 2014) and the interactive effects of cumulative stress and impulsivity on alcohol consumption (Fox et al, 2010). By combining the AUDIT and clinical assessment of alcohol use, we may examine the effects of drinking problems and duration of use on inhibitory control.…”
Section: Introductionmentioning
confidence: 99%